The Impact of Negative Facts on the Spiritual Appearance of Girls is A Problem - Kasimova Ozoda Khudoynazarovna; Saidboboeva Nilufar Khasan kizi (Genius Publishing Group, 2022)
In this article analyses types and the forms some negative factor influencing upon spiritual-moralized look girl-students. The author opening the pedagogical possibilities a cooperation family -mahalla and educational institutions in removal these negative factors
Keywords: students; spirituality; morality; spiritual appearance